Metaphor comprehension in preschool children - Ariel Starr; Sahana Sridhar; Taylor Petersen (Language Development Research, 2025)
Recent work suggests that though young children can comprehend metaphors based on shared perceptual or functional features, comprehending metaphors based on abstract relations presents a greater challenge. We conducted two pre-registered studies (n = 276; mean age = 3.7 years; 146 female, 49% white) to investigate children’s ability to understand metaphors based on perceptual and abstract similarities. We also assessed how children’s language learning environments (monolingual or bilingual) relate to metaphor comprehension. Children were successful in understanding both types of metaphors. In addition, monolingual and bilingual children were equally proficient in metaphor comprehension. These findings highlight the sophisticated ways that preschool-age children can use their rapidly developing lexicons.